COGNITIVE WARFARE AS A STRATEGIC AVANT-GARDE: A DIALECTICAL PERSPECTIVE ON STRATEGIC THINKING - Checa Rubio, Marcos (Journal of the Spanish Institute for Strategic Studies, 2025)
This article explores the capacity to develop a comprehensive understanding of reality through the materialist dialectic approach to knowledge. To achieve this, a critique is conducted from the dialectical perspective of modern scientific knowledge, which tends to follow a fragmented approach to knowledge, hindering adaptation to the current geostrategic context. Furthermore, it is shown how cognitive warfare has taken a central role within national security strategies, emerging as a superior phase of strategic thinking in itself. In this regard, it is highlighted how cognitive warfare, in its strategic form, extends beyond the military sphere, permeating various social and political domains, integrating the nexus between war as the continuation of politics by other means and providing conscious state direction. Through this approach, the article examines the strategic approaches of China, Russia, and the United States, concluding that the first two are in a position of strategic advantage due to the holistic vision provided by their approach to knowledge.